1979
DOI: 10.1002/cpt197925133
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorothiazide and spironolactone in hypertension

Abstract: A double-blind study of hydrochlorothiazide and spironolactone, alone and in combination, was conducted in 49 patients with mild-to-moderate essential hypertension after a 4-wk placebo washout period. In the whole group mean arterial blood pressure fell to levels of less than or equal to 107 mm Hg or declined by more than 15 mm Hg in 78% of the patients after twelve weeks of treatment. Sixty-nine percent of patients receiving hydrochlorothiazide alone developed serum potassium levels lower than 3.5 mEq/L; seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 3 publications
2
26
0
2
Order By: Relevance
“…In two studies that defined hyperkalemia as serum potassium 5.5 mEq/L, the incidence of hyperkalemia ranged from 3% to 6% at spironolactone doses of 12.5 to 400 mg/day. 23,24 At the 5.5 mEq/L threshold, the incidence of eplerenone-induced hyperkalemia ranged from 1%-3% at doses of 50-200 mg/day. 25 -27 For studies that used a serum potassium threshold 6.0 mEq/L, the incidence of hyperkalemia ranged from 0% to 11% at eplerenone doses of 50-200 mg/day.…”
Section: Tolerability Endocrine Effectsmentioning
confidence: 99%
“…In two studies that defined hyperkalemia as serum potassium 5.5 mEq/L, the incidence of hyperkalemia ranged from 3% to 6% at spironolactone doses of 12.5 to 400 mg/day. 23,24 At the 5.5 mEq/L threshold, the incidence of eplerenone-induced hyperkalemia ranged from 1%-3% at doses of 50-200 mg/day. 25 -27 For studies that used a serum potassium threshold 6.0 mEq/L, the incidence of hyperkalemia ranged from 0% to 11% at eplerenone doses of 50-200 mg/day.…”
Section: Tolerability Endocrine Effectsmentioning
confidence: 99%
“…8,9 Hydrochlorothiazide (HCTZ) is a thiazide diuretic which is commonly used for the treatment of essential hypertension, at recommended doses of 12.5 mg or 25 mg. 10 In published clinical studies, HCTZ has been shown to act additively in combination with several classes of antihypertensive medication. [11][12][13][14] In addition to its diuretic effect HCTZ is known to activate the renin-angiotensin system.…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic hypokalemia may be a greater risk factor for sudden death than has previously been recognized 1 " 3 and invariably occurs when proximal tubule or loop diuretics are used. 4 Diuretic-induced increases in uric acid may precipitate gout in rare patients or predispose them to urolithiasis. In addition, uric acid has been shown to be a risk factor for coronary artery disease.…”
mentioning
confidence: 99%